The prevalence of inherited thrombophilic polymorphisms in an asymptomatic Australian antenatal population - Said, J.; Brennecke, S.; Moses, Eric; Walker, S.; Monagle, P.; Campbell, J.; Bryant, V.; Borg, A.; Higgins, J. (Wiley-Blackwell Publishing Asia, 2008)
Aim: Inherited thrombophilic polymorphisms have been linked to pregnancy-related thromboembolism and other adverse pregnancy outcomes. As there are limited data on the prevalence of these polymorphisms in Australian populations, we aimed to assess this in an antenatal population. Methods: Healthy nulliparous women (n=2031) were recruited to this study. The women had no past or family history of venous thromboembolism. Women were excluded if they or a family member was known to be a carrier of any thrombophilic marker. Genotyping from venous blood for the factor V Leiden, prothrombin 20210A, MTHFR 611 and 1298 and thrombomodulin C1418T polymorphisms was undertaken. Results: Key findings were that 101 of 2019 (5.30, 95% confidence interval 4.36-6.31%) women tested were heterozygous carriers of factor V Leiden and one was homozygous (0.05, 0-0.21%); 2.43% of women were heterozygous carriers of the prothrombin gene mutation (1.80-3.20%) while no women were homozygous for this mutation; 11.62% (10.22-13.02%) and 9.98% (8.61-11.29%) were homozygous for the MTHFR 611 and 1298 polymorphisms, respectively, and 3.43% (2.63-4.22%) of women were homozygous for the thrombomodulin polymorphism. Conclusions: The prevalence of these polymorphisms is consistent with previously published data in Caucasian populations. These data will provide the basis for further assessment of the relationship between poor pregnancy outcome and these inherited thrombophilic polymorphisms in an asymptomatic antenatal population. © 2008 The Royal Australian and New Zealand College of Obstetricians and Gynaecologists.